Research Skills of Prospective Biology Teacher: An Analysis for Development Needs - Amelia, Trisna; Liliasari (Pedagogi Hayati, 2023)
College graduates, including prospective biology teachers, should possess excellent research skills. This competency has become an objective profile for graduates of Biology education department, however it has not been adequately developed during the lecture process. This study was conducted to determine the extent to which research skills have been mastered by prospective biology teacher in learning at universities and to determine the need for developing research skills. Research skills are defined as skills using information literacy and basic biology laboratory skills related to research. This study employed a descriptive approach, involving document review and survey. An analysis of curriculum documents and lesson plans was carried out to explore lecture designs that prepare students' research skills. A total of 25 graduates were involved in a perception survey of how important research skills are for them in the workplaces. 27 final year students were also involved in providing self-assessments about their ability to master information literacy and basic biology laboratory skills. Data was analyzed qualitatively and quantitatively. The study resulted that the researcher profile is one of the targets for graduates of biology education study programs but has not been supported by course designs. Research skills are needed by graduates in the workplaces and are very relevant to support their careers. Information literacy and basic biology lab skills have not been fully mastered by final year students. There is an urgency to equip students with more adequate skills so that students are better able to carry out research, including completing their studies.